Environmental management in SMEs: organizational and sectoral determinants in the context of an Outermost European Region - Armas-Cruz, Yaiza; Gil-Soto, Esperanza; Oreja-Rodríguez, Juan Ramón (Journal of Business Economics and Management, 2017)
This paper evaluates the environmental behavior of smes in the Canary Islands (Spain), one of the Outermost European Regions. The islands’ fragile socioeconomic systems and scarce resources noticeably condition the competitiveness of their firms. An empirical analysis ranks environmental protection practices in smes and identifies differences on the basis of size and business sector. In addition, groups of firms with different environmental behavior are identified to facilitate the design of environmental policies, improve effectiveness in decision making and the more efficient use of resources. From a theoretical perspective, this paper contributes to the gap identified by the precursors of the Natural Resource-Based View of the firm by analyzing specific resource combinations that each firm can use to improve its environmental performance and achieve competitive advantages. The firms best positioned to develop the dynamic capabilities needed are identified not only considering the physical environment, but also the socio-economic one and key intangible resources are measured that shape firms’ environmental strategy.